Executive control in bilingual aphasia: a systematic review. Issue 1 (18th January 2022) - Mooijman, Saskia; Schoonen, Rob; Roelofs, Ardi; Ruiter, Marina B.
Abstract: Much research has been dedicated to the effects of bilingualism on executive control (EC). For bilinguals with aphasia, the interplay with EC is complex. In this systematic review, we synthesize research on this topic and provide an overview of the current state of the field. First, we examine the evidence for EC deficits in bilingual persons with aphasia (bPWA). We then discuss the domain generality of bilingual language control impairments. Finally, we evaluate the bilingual advantage hypothesis in bPWA. We conclude that (1) EC impairments in bPWA are frequently observed, (2) experimental results on the relationship between linguistic and domain-general control are mixed, (3) bPWA with language control problems in everyday communication have domain-general EC problems, and (4) there are indications for EC advantages in bPWA. We end with directions for experimental work that could provide better insight into the intricate relationship between EC and bilingual aphasia.